The Impact of Accrual-Based Accounting in Financial Reporting of the Regional Revenue Agency of Surabaya City - Lesar, William Stephanus Tristan; Riko Setya Wijaya; Marseto (UPT Publikasi Ilmiah UNISBA, 2025)
This Article will discuse the implementation of accrual-based accountinng in financial reporting at Surabaya Regional Revenue Agency using Accrual-based accouting. In accordance wth Government Regulation Number 71 of 2010, requires tthe recognition of economic transaction when they occur, not when the tax is recieved or paid. The method use is a descriptive qualitative approach with data collection through interviews, document analysis, and real action that implemented when the activity is on going. The focus of writing this article is data collection on LO recei The conclusion that can be drawn from this article is that technological developments have a significant impact on the process of journalizing financial reports. With the help of website pages on current computer devices